Sistem Pendukung Keputusan Penerima Beasiswa UMN dengan Profile Matching - Marvin Apriyadi; Seng Hansun (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2018)
This paper describes about the design and development of UMN scholarship decision support system using Profile Matching method. At Universitas Multimedia Nusantara (UMN), there are scholarships for students in order to ease the burden of education costs. There are achievement scholarships, scholarships for students whose parents died, and non-academic scholarships. Decision support systems play an important role in the termination of the final decision, and therefore this application is built by implementing the method of Profile Matching to aid in the selection of the scholarship decisions for students whose parent were died and non-academic scholarship. Profile Matching is a method that aims at taking decisions by assuming that there is an ideal level of predictor variables that must be met by the subjects studied, instead of the minimum rate that must be met or passed. From the results, it can be concluded that this method successfully implemented into applications that can help in decision making process. Result of user satisfaction level for this application is 72%, the result of manual calculation with the application calculation results is not much different so that this application can assist in supporting the UMN scholarship decision. Index Terms— decision support system, non-academic scholarship, Profile Matching, scholarships for student whose parents died, UMN